TELAAH TERHADAP DRAF KHI PERSPEKTIF SEJARAH SOSIAL HUKUM - Muttaqien, Dadan (Al-Mawarid Jurnal Hukum Islam, 2005)
Indonesian President decree No. 1 year 1991 regarding spreading The Compilation of Islamic Law that addresses to The Minister of Religious Affairs as representation of Islamic Law that will be applied as foundation of Moslem in Indonesia. Then, its development, the position of this regulation or this decree will be graded to become the act so some articles of this decree need revising in accordance with Indonesian local culture. At the same time emerging controversial thought because of growing and developing by Islamic liberal, pluralist, emancipatorist or gender community. These communities encounter toward revised Islamic Law Compilation, so emerging the controversial ideas in Indonesia.